Women's Health in Central America: The Complexity of Issues and the Need to Focus on Indigenous Healthcare - Pérez Sánchez, Alice Lorena (2013)
The Central American (CA) isthmus consists of seven countries including Belize, Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua and Panama, some of the poorest countries in the world. Over the past twenty years, CA has made good progress in improving the health status of their populations. Analysis of the peer-reviewed literature, as well as national and international reports show that life expectancy at birth has increased and child mortality rates have fallen. Maternal mortality ratios (MMR) have declined by approximately 33%, however the MMRs for indigenous women remain at unacceptable levels. Despite the advances, made in many CA countries, the overall health status remains well below Latin American averages. In fact, in most CA countries, poor health outcomes are increasingly concentrated geographically among the poor and indigenous populations. Considering indigenous people make up the second largest population group in CA, any improvements in healthcare should significantly improve the health statistics for these countries. For these populations, the integration of local cultural practices and traditional healing methods with modern medicine and healthcare facilities is critical for acceptance. Investigations and analyses of local cultures, knowledge and traditional medicine practices should be used to determine the factors that contribute to poor health in these populations. Local health educational programs are needed, especially those that would involve men (spouses), families and entire communities. Furthermore, manywomen’s reproductive issues still need to be addressed, particularly those that focus specifically on maternal mortality and cancer. For reductions in maternal mortality, El Salvador and Costa Rica may be good examples to follow. Access to inexpensive (or free) healthcare that is culturally sensitive and community based, particularly for indigenous women, would greatly improve the overall health. The major stumbling blocks to progress are that the funding for programs to reduce maternal mortality is woefully inadequate and that there has not been a focus on improving healthcare for indigenous women.